"A good investment?": State sponsorship of terrorism as an instrument of Iraqi foreign policy (1979-1991) - Kirchner, Magdalena (Cambridge review of international affairs, 2014)
Governmental support for nonstate actors designated as terrorist organizations is not only a policy that carries significant international and domestic costs; it further poses a theoretical challenge to structural realist thinking about alliance politics in international relations. By debating, firstly, the utility of terrorism as a means to influence systemic power distribution, and, secondly, the functional equality of nonstate actors, this article considers under what conditions state sponsored terrorism occurs despite the expected security loss. Drawing on the example of Iraq between 1979 and 1991, the assumption that the interplay of external security challenges—as well as domestic dissent as an intervening, unit-level factor—affects governmental alignments with terrorist groups will be reviewed in the cases of the Iranian Mujahedin al-Khalq Organization, the Syrian Muslim Brotherhood and armed Palestinian factions. The article concludes by addressing whether state sponsorship of terrorism is inevitably linked to policy failure or whether it could be seen as a good investment to balance external and internal security challenges successfully.